On Determining the Volume of Repeated and Non-Repeated Sampling in the Preparation of Clinical Studies - Kozhyna, Olga S.; Pihnastyi, O. M. (ARC Publications, 2019)
In this article, non-repeatable and repeatable sampling methods were analyzed. Main objectives connected with the use of sampling research method were determined. The problem of non-repeatable sampling amount defining at a given rate of bronchial asthma prevalence was analyzed. Key preconditions and assumptions used when constructing the expression to determine the non-repeatable and repeatable sample amount were depicted.
Keywords: non-repeatable sample amount; repeatable sample amount; bronchial asthma; ISAAC; research methods; statistical population feature